The Job Satisfaction of District Officers in the Developing State Like; Pakistan A Survey of Local Government of Khyber Pakhtunkhwa (Global Journal of Management and Business Research, 2014)
The Job satisfaction of district officers in Pakistan is affected by different factors like, Terrorism, political Instability, poverty and dysfunction of bureaucracy. There is uniqueness as well as differences in the perception of the officers about job satisfaction from situation to situation and from organization to organization. There are consensus among the researchers that job satisfaction increases employee's productivity, commitment and Involvement and decreases absenteeism and turnover. This study is intended to pinpoint the causes, consequences of job satisfaction in developing state like; Pakistan.
Keywords: job satisfaction (js); district officers (do#x2019; s) factors of job satisfaction (fjs)